2009
DOI: 10.1136/bcr.07.2008.0412
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis, rhabdomyolysis and multi-organ failure resulting from statin use

Abstract: While there is good evidence suggesting improved outcomes with use of high dose statins, the potential drug interactions and adverse effects need close attention. All patients started on statin therapy should be counselled regarding the signs and symptoms of muscle injury, particularly those who are on drugs that may have an interaction. In this patient the Naranjo probability scale revealed a probable adverse reaction associated with atorvastatin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In 2009, Muthuram et al [10] reported the case of a 77-year-old man diagnosed with aortic stenosis, whose atorvastatin dose was increased from 40 mg to 80 mg 6 months before presentation. He presented with acute hepatitis, rhabdomyolysis, and acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Muthuram et al [10] reported the case of a 77-year-old man diagnosed with aortic stenosis, whose atorvastatin dose was increased from 40 mg to 80 mg 6 months before presentation. He presented with acute hepatitis, rhabdomyolysis, and acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…7 As shown in Table 1, there are 11 published cases of atorvastatin-induced rhabdomyolysis including our case report, with 7 cases occurring in patients who are 65 years or older and 3 cases occurring in patients who are 76 years and older. [12][13][14][15][16][17][18][19][20][21] In addition to age, several patients had other risk factors for rhabdomyolysis. For example, 2 patients had a history of chronic renal disease and 1 patient had a history of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%